Sentiment Ontology Analysis for Adverse Drug Effect (Medico Legal Update, 2019)
Adverse drug reactions (ADR) are happen more frequently based on different drugs. ADR should bemonitored by Pharmacovigilance. Due to drug usage of single dose or combine dose ADR are happen. ADRcan’t be monitored in INDIA because of not follow the physician direction and also self-medication. Most ofthe Indians used drug store or online to purchase drugs. The proposed method utilised different websites andonline drugs reviews with sentiment analysis and conjugate gradient method in neural network. In output,we propose the best way to monitor the ADR and drug harmfulness.